Fine tuning of globin gene expression by DNA methylation. - Alon Goren; Giora Simchen; Eitan Fibach; Piroska E Szabo; Keiji Tanimoto; Lyubomira Chakalova; Gerd P Pfeifer; Peter J Fraser; James D Engel; Howard Cedar (PLoS ONE)
Expression patterns in the globin gene cluster are subject to developmental regulation in vivo. While the gamma(A) and gamma(G) genes are expressed in fetal liver, both are silenced in adult erythrocytes. In order to decipher the role of DNA methylation in this process, we generated a YAC transgenic mouse system that allowed us to control gamma(A) methylation during development. DNA methylation causes a 20-fold repression of gamma(A) both in non-erythroid and adult erythroid cells. In erythroid cells this modification works as a dominant mechanism to repress gamma gene expression, probably through changes in histone acetylation that prevent the binding of erythroid transcription factors to the promoter. These studies demonstrate that DNA methylation serves as an elegant in vivo fine-tuning device for selecting appropriate genes in the globin locus. In addition, our findings provide a mechanism for understanding the high levels of gamma-globin transcription seen in patients with Hereditary Persistence of Fetal Hemoglobin, and help explain why 5azaC and butyrate compounds stimulate gamma-globin expression in patients with beta-hemoglobinopathies.